IN SITU OPTHALMIC GEL WITH ION ACTIVATED SYSTEM - Kurniawansyah, Insan Sunan; Rusdiana, Taofik; Wahab, Habibah A.; Subarnas, Anas (International Journal of Applied Pharmaceutics, 2019)
In situ gel with ion activated system which occurs as triggered by a change in the ionic strength. Osmotic gradient is a factor that determines the rate of gelation on the surface of the gel. Polymers play an important role in drug delivery from their dosage forms. Polymeric in gelling systems provides longer drug release compared to conventional delivery systems. The use of biodegradable and biocompatible polymers for in situ gel formulation makes the drug delivery system acceptable and controlled. Thus the continuous and prolonged release of the drug, biocompatibility characteristics makes the dose gel form in situ reliable. Polymers that are used in ion activated in situ gelation can be various, such as gelrite gellan gum, alginates, deacetylated gellan gum, anionic polymers (carbopol), cationic polymer (chitosan), non-ionic polymers (HPMC, Methylcellulose), thiolated polymer (thiomers), carbomer (polymer used in ophthalmic), polycarbophil (polymer used in ophthalmic). This review is written based on the data or information obtained by using several search engines and several scientific journals, using the keywords in situ gel with polymers, ion activated the system, and limited search years in 2010 and above.